2013
DOI: 10.14245/kjs.2013.10.3.160
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic Changes of Anterior Cervical Discectomy and Fusion Using Allograft and Plate Augmentation: Comparison of Using Fixed and Variable Type Screw

Abstract: ObjectiveTo evaluate radiologic result of anterior cervical discectomy and fusion with allobone graft and plate augmentation, and the change of radiologic outcome between screw type and insertion angle.MethodsRetrospective review of clinical and radiological data of 29 patients. Segmental angle, height and screw angles were measured and followed. The fusion rate was assessed by plain radiography and CT scans. We divided the patients into two groups according to screw type and angles. Group A: fixed screw, Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Therefore, recent ACDF studies tend to mainly focus on alternative graft materials with comparable outcomes without the problems related to autograft. As anterior plating becomes more popular, an increasing number of articles support allograft using ACDF with plate augmentation, showing improved postoperative clinical and radiological outcomes [6,18,20-23]. When the plate is augmented, fusion rate was reported to be similar or even better than ACDF without plate fixation [18,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, recent ACDF studies tend to mainly focus on alternative graft materials with comparable outcomes without the problems related to autograft. As anterior plating becomes more popular, an increasing number of articles support allograft using ACDF with plate augmentation, showing improved postoperative clinical and radiological outcomes [6,18,20-23]. When the plate is augmented, fusion rate was reported to be similar or even better than ACDF without plate fixation [18,24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that treatment using cervical plates significantly reduces graft-related complication rates in one- and two-level ACDF with allograft cortical bone, with significantly enhanced arthrodesis [6,21,25]. In particular, Kaiser et al [21] reported a significant decrease in the graft-related complication rate with anterior plating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of two-level ACDF using 4 mm as the reference, the presence of subsidence was defined when the difference was larger than 4 mm ( Fig. 1 ) 21) .…”
Section: Methodsmentioning
confidence: 99%
“…Many studies reported that subsidence rate varies between 23.4-50.5% 27 , 44) . There has been reported the risk factors associated with subsidence.…”
Section: Discussionmentioning
confidence: 99%